Time to maximum clinical improvement following minimally invasive chevron and Akin osteotomies (MICA) in hallux valgus surgery. Issue 7 (October 2022) - Lewis, T.L.; Ray, R.; Gordon, D.J.
Abstract: Background: There is increasing evidence of positive improvement in clinical and radiological outcomes following minimally invasive hallux valgus deformity correction surgery (MIS). This study investigated the rate of improvement in clinical patient reported outcome measures (PROMs) following MIS as this is not well understood. Methods: Between July 2014 and July 2019, data was prospectively collected from consecutive patients pre-operatively and at 6, 12, and 24 months following third-generation minimally invasive chevron and Akin osteotomies (MICA). Radiographic deformity and correction was assessed using weight-bearing radiographs pre-operatively and 6 weeks post-operatively. The primary outcome measure was the change in Manchester Oxford Foot Questionnaire (MOXFQ) score at each time point. Secondary outcomes include radiographic deformity correction, health-related quality of life PROMs and exploration of cases where PROMs did not improve. Results: There were 202 feet with complete PROM data for every time point. There was a statistically significant improvement in MOXFQ Index score at each time point (p < 0.05) following MICA surgery. The majority of the improvement occurred within the first 6 months. A subgroup of 17 feet (8.4%) were identified which had worse MOXFQ Index scores 6 months following MICA. For 14 feet in this subgroup (82.4%), the MOXFQ Index score subsequently improved over time such that by two years, their score had significantly improved compared to their pre-operative score. Conclusion: The majority of PROM improvement with MICA is gained by 6 months post-operatively but further significant improvement can be seen up to 2 years. Those patients who have not improved at 6 months, are likely to do so with time. Level of evidence: IV.